Locality in the Folk Songs of Gulmi, Palpa and Arghakhanchi - Ghimire, Ram Prasad (Vox Batauli, 2024)
This article draws on the folk songs of Gulmi, Palpa and Arghakhanchi with special focus on how they reflect and represent the sense of locality. Most of the folk songs that carry with them the sense of locality in the given districts are wali, Teej songs, savai and bhajan. People in these districts sing their own local folk songs to express their feelings deeply attached with their own local objects, places, people and gods and goddesses. I studied these folk songs in connection to the local beliefs and sensibilities that are regularly attached with what they do and anticipate in their actual local life. Anyway, the given folk songs duly reflect the local colors of the regional landscape, cultures, memories and music that have their own beauty and taste.